2020
DOI: 10.1177/2040620719896961
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of intestinal microbiota in hematopoietic stem-cell transplantation

Abstract: The gut microbiota (GM) is able to modulate the human immune system. The development of novel investigation methods has provided better characterization of the GM, increasing our knowledge of the role of GM in the context of hematopoietic stem-cell transplantation (HSCT). In particular, the GM influences the development of the major complications seen after HSCT, having an impact on overall survival. In fact, this evidence highlights the possible therapeutic implications of modulation of the GM during HSCT. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 144 publications
0
39
0
Order By: Relevance
“…Higher diversity of intestinal microbiota at the time of neutrophil engraftment was associated with lower mortality [9]. The microbiota can be used as predictor of mortality in allo-HSCT [10], and the constitution of the intestinal microbiota at neutrophil engraftment and GM score can predict the development of aGvHD following myeloablative allo-HSCT [24,25]. These results supported the idea for modulation of the GM in patients with HSCT.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Higher diversity of intestinal microbiota at the time of neutrophil engraftment was associated with lower mortality [9]. The microbiota can be used as predictor of mortality in allo-HSCT [10], and the constitution of the intestinal microbiota at neutrophil engraftment and GM score can predict the development of aGvHD following myeloablative allo-HSCT [24,25]. These results supported the idea for modulation of the GM in patients with HSCT.…”
Section: Introductionmentioning
confidence: 54%
“…Most recent study showed that microbiota can be used as predictor of mortality in allo-HSCT [9]. Many studies have showed that targeted modulation of GM in patients with HSCT has potential therapeutic implications [10]. In this review, we summarize the advance of therapies targeting GM in patients with HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher risk of blood stream infection caused either by vancomycin-resistant Enterococcus or Gram-negative bacteria (e.g., Es. coli or Klebsiella pneumoniae ) was reported, and post-engraftment vancomycin-resistant Enterococcus colonization was associated with increased mortality ( Ford et al, 2017 ; Tamburini et al, 2018 ; Zama et al, 2020 ).…”
Section: Impact Of the Gut Microbiota On Gvhdmentioning
confidence: 99%
“…Reciprocally, the intestinal microbiota can regulate hematopoiesis and promote myeloid differentiation ( Shono and van den Brink, 2018 ). Intestinal bacteria are potent modulators of systemic immune responses ( Zama et al, 2020 ). Alteration in the intestinal microbiota is associated with graft-versus-host disease (GVHD), bacteremia, disease relapse, and mortality after allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%